RESEARCH ON THE HEAVY METALS IN SURFACE SEDIMENTS, IN STRÂMTORI-FIRIZA RESERVOIR, SITUATED IN N-W OF ROMANIA - SMICAL, Irina; MUNTEAN, Adriana; CIURTE, Dan Lucian; MICLE, Valer (Studia Universitatis Babeș-Bolyai Chemia, 2020)
In this study referring to the surface sediments quality of Strâmtori-Firiza reservoir, a series of heavy metals like arsenic, cadmium, copper, lead and zinc were investigated from 2017 to 2019. The samples analysis and interpretation of the results for 18 samples taken from surface sediments indicated that the correlation coefficients calculated for the metallic elements showed a significant correlation between them. Thus, highlighting their same origin in the composition of the studied surface sediments, only the value of the coefficient between As and Pb implies a statistically significant correlation. Pollution indices, calculated for each sampling site, indicated anthropogenic unpolluted surface sediments. The potential ecological risk (RI), calculated for assessing the toxicity risk related to surface benthic biomass, showed that the potential ecological risk for biological life in surface sediments was low.